Demographic and Genetic Evaluation of an American Marten Reintroduction - Swanson, Bradley J.; Peters, L. Robert; Kyle, Christopher J. (Journal of Mammalogy, 2006)
Reintroduced populations are generally smaller and more isolated than native populations; thus even when reintroduced populations are demographically stable, a lack of genetic variation may present a threat to long-term persistence. We examined the demographic structure and genetic variation of the marten reintroduction into the Upper Peninsula of Michigan. Male : female and juvenile : adult female ratios indicate that the Michigan population is demographically stable. Michigan martens had higher allelic diversity ( A = 7.4) compared to the average diversity found among Canadian populations ( A = 5.8) and similar levels of observed heterozygosity ( H Canadian = 0.64, H Michigan = 0.63), excluding Newfoundland martens. We found no significant differences in the allelic diversity or heterozygosity between the reintroduced Michigan population and the source population for the reintroduction, that of Chapleau, Ontario. Surprisingly, we found no evidence of a genetic bottleneck in the Michigan population. We suggest that the genetic success of this reintroduction is a result of the multiple reintroductions and subsequent intrastate translocations that mimicked gene flow. The success was further aided by the presence of small remnant populations that remained in Michigan, as evidenced by the presence of private alleles in Michigan.